2009
DOI: 10.2746/095777309x462
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal rupture with herniation of the urinary bladder through the scrotal fascia in a Shetland pony foal

Abstract: Herniation of the urinary bladder in the inguinal region has not previously been described in the horse. A case of inguinal rupture with herniation of the bladder through the scrotal fascia in a 3-month-old Shetland pony, diagnosed by external palpation, urinary catheterisation and external ultrasonographic examination is reported. Surgical management of the case was by dissection of the scrotal fascia, partial cystectomy and unilateral castration. During the period of hospitalisation the only complication was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
2
8
0
3
Order By: Relevance
“…Inguinal rupture of horses is rare, based on the scarcity of reports describing horses with this condition. Even though rupture must be associated with a traumatic event, this event is not always obvious, as in the case of inguinal rupture described by Cousty et al. (2010) in this issue.…”
Section: Aetiologymentioning
confidence: 95%
See 1 more Smart Citation
“…Inguinal rupture of horses is rare, based on the scarcity of reports describing horses with this condition. Even though rupture must be associated with a traumatic event, this event is not always obvious, as in the case of inguinal rupture described by Cousty et al. (2010) in this issue.…”
Section: Aetiologymentioning
confidence: 95%
“…The inguinal rupture was thought to have occurred 4 weeks previously when the horse fell. The case of inguinal rupture reported by Cousty et al. (2010) is interesting not only because so few horses with the condition have been reported but also because of the apparently long duration of the condition and because the viscus that entered the rent was bladder rather than intestine.…”
Section: Aetiologymentioning
confidence: 96%
“…The orchiectomy enabled such identification and allowed seeing that the hernial content was a portion of the omentum, although it is atypical, since segments of the small intestine are the hernial content in most cases (Kovac et al, 2018). Other intestinal loops can be found in the hernial sac; among them, one finds the large colon (Ivens et al, 2009;Robinson and Carmalt, 2009), in addition to other organs such as the bladder (Cousty et al, 2010). However, in these cases, the horses were small-sized breed foals, whereas the animal in the present case report was an adult Criollo stallion.…”
Section: Discussionmentioning
confidence: 52%
“…On the other hand, acquired non-strangulated hernias are not often diagnosed (Bach and Ricketts, 1974). The herniation of other intestinal loops or other organs is rarely reported; the reported cases mainly refer to young animals (Ivens et al, 2009;Robinson and Carmalt, 2009;Cousty et al, 2010) or to horses who were recently exposed to orchiectomy procedures (Schumacher, 2006;Ivens et al, 2009). One of the clinical signs observed in animals presenting this condition lies on increased scrotal volume (Stick, 2006;Kovac et al, 2018), which is also observed in several pathologies involving the testes and the epididymis (Claes and Stout, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…O principal sinal clínico de HI é aumento de volume de consistência macia na região inguinal (SMEAK, 2007;COUSTY et al, 2010;ABREU et al, 2013;BORGES et al, 2014). A história e a palpação são úteis para o diagnóstico, o qual é confirmado pela redução da hérnia, palpação do anel inguinal (SMEAK, 2007;BORGES et al, 2014) e exames de imagem (SMEAK, 2007;ABREU et al, 2013).…”
Section: Introductionunclassified